Domestic-office work-load and coping mechanisms of female bankers in Ibadan, Nigeria (2014)
Banking jobs have overtime been perceived to be tasking and time demanding, especially for married women in a patriarchal community like Ibadan. This, coupled with the roles women play as wives and mothers, have implications for women’s psychological wellbeing and work performance. The paper, thus, attempts to examine the challenges of combining office and domestic works and the coping mechanisms adopted by married female bankers using the role strain and conflict theory as frameworks for explanation. Questionnaire was administered to 110 married female bankers who were purposively selected from five banks in Ibadan, while in-depth interview was conducted with 10 of these bankers from the senior cadre. Quantitative data were analyzed using descriptive and inferential statistics, while qualitative data were presented using content analysis. Findings revealed that the majority (69 percent) of the respondents experienced stress, fatigue, depression and frustration in work performance. Some others experienced role conflict such as piling up backlog of work (73 percent), lack of adequate attention and care for kids (62 percent) and husbands (64 percent). Coping strategies included waking up early to do household chores and closing late at work to complete office works, recruiting housemaids, postponing domestic chores and proper planning. There was no significant relationship between the educational status of female bankers and recruitment of housemaids (X2=6.22, df=3,P<0.05).The study recommends proper planning by individuals and development of policies by other workforce and banking sector targeted at reducing the pressures of combining office and domestic work for married women